De novo design based identification of potential HIV-1 integrase inhibitors: A pharmacoinformatics study. (October 2020) - Shinde, Pooja Balasaheb; Bhowmick, Shovonlal; Alfantoukh, Etidal; Patil, Pritee Chunarkar; Wabaidur, Saikh Mohammad; Chikhale, Rupesh V.; Islam, Md Ataul
Graphical abstract: Highlights: Complex between BI-224436 and HIV-1 integrase was used to design novel anti-HIV inhibitors. The de novo approach available in LigBuilder was used. A number of criteria was used to narrow down the chemical space of initial designed 80, 000 inhibitors. Different pharmacokinetics parameters were checked for final proposed molecules. MD simulation was performed of HIV-1 integrase complex with proposed molecules. Abstract: In the present study, pharmacoinformatics paradigms include receptor-based de novo design, virtual screening through molecular docking and molecular dynamics (MD) simulation are implemented to identify novel and promising HIV-1 integrase inhibitors. The de novo drug/ligand/molecule design is a powerful and effective approach to design a large number of novel and structurally diverse compounds with the required pharmacological profiles. A crystal structure of HIV-1 integrase bound with standard inhibitor BI-224436 is used and a set of 80, 000 compounds through the de novo approach in LigBuilder is designed. Initially, a number of criteria including molecular docking, in-silico toxicity and pharmacokinetics profile assessments are implied to reduce the chemical space. Finally, four de novo designed molecules are proposed as potential HIV-1 integrase inhibitors based on comparative analyses. Notably, strong binding interactions have been identified between a few newly identified catalytic amino acid residues and proposed HIV-1 integrase inhibitors. For evaluation of the dynamic stability of the protein-ligand complexes, a number of parameters are explored from the 100 ns MD simulation study. The MD simulation study suggested that proposed molecules efficiently retained their molecular interaction and structural integrity inside the HIV-1 integrase. The binding free energy is calculated through the Molecular Mechanics Poisson-Boltzmann Surface Area (MM-PBSA) approach for all complexes and it also explains their thermodynamic stability. Hence, proposed molecules through de novo design might be critical to inhibiting the HIV-1 integrase.